Principles of Optimization Techniques to Combinatorial Optimization Problems and Decomposition (International Journal of Scientific Research and Management (IJSRM), 2015)
This paper focused on the fundamental concept and solution approaches to the combinatorial optimisation techniques. The construct of the effective methods of this paper are based on the integrations of Constraints Programming (CP), Integer Programming (IP) and local search (LS) to tackle combinatorial optimization problem from different application areas like the nurse scheduling and the portfolio selection problems. These techniques demonstrate the effectiveness of the method as well as knowledge of the quality of the solution